Efficacy of a standardised acupuncture approach for women with bothersome menopausal symptoms: a pragmatic randomised study in primary care (the ACOM study) - Lund, Kamma Sundgaard (BMJ Open, 2019)
OBJECTIVE: To investigate the efficacy of a standardised brief acupuncture approach for women with moderate-to-severe menopausal symptoms. DESIGN: Randomised and controlled, with 1:1 allocation to the intervention group or the control group. The assessor and the statistician were blinded. SETTING: Nine Danish primary care practices. PARTICIPANTS: 70 women with moderate-to-severe menopausal symptoms and nine general practitioners with accredited education in acupuncture. INTERVENTION: The acupuncture style was western medical with a standardised approach in the predefined acupuncture points CV-3, CV-4, LR-8, SP-6 and SP-9. The intervention group received one treatment for five consecutive weeks. The control group was offered treatment after 6 weeks. MAIN OUTCOME MEASURES: Outcomes were the differences between the randomisation groups in changes to mean scores using the scales in the MenoScores Questionnaire, measured from baseline to week 6. The primary outcome was the hot flushes scale; the secondary outcomes were the other scales in the questionnaire. All analyses were based on intention-to-treat analysis. RESULTS: 36 participants received the intervention, and 34 participants were in the control group. Four participants dropped out before week 6. The acupuncture intervention significantly decreased hot flushes: Δ −1.6 (95% CI [−2.3 to −0.8]; p<0.0001), day-and-night sweats: Δ −1.2 (95% CI [−2.0 to −0.4]; p=0.0056), general sweating: Δ −0.9(95% CI [−1.6 to −0.2]; p=0.0086), menopausal-specific sleeping problems: Δ −1.8 (95% CI [−2.7 to −1.0]; p<0.0001), emotional symptoms: Δ −3.4 (95% CI [−5.3 to −1.4]; p=0.0008), physical symptoms: Δ −1.7 (95% CI [−3 to −0.4]; p=0.010) and skin and hair symptoms: Δ −1.5 (95% CI [−2.5 to −0.6]; p=0.0021) compared with the control group at the 6-week follow-up. The pattern of decrease in hot flushes, emotional symptoms, skin and hair symptoms was already apparent 3 weeks into the study. Mild potential adverse effects were reported by four participants, but no severe adverse effects were reported. CONCLUSIONS: The standardised and brief acupuncture treatment produced a fast and clinically relevant reduction in moderate-to-severe menopausal symptoms during the six-week intervention. No severe adverse effects were reported. TRIAL REGISTRATION NUMBER: NCT02746497; Results.